CRITICAL REVIEW OF HERBS ACTING ON PRANAVAHA SROTOVIKAR (International Journal of Ayurveda and Pharma Research, 2015)
The human body contains several channels through which the Doshas, Dhatus and Malas travel which are called as Srotamsi. There are thirteen Abhyantra srotamsi, each of which relates to specific organs, and are increased and vitiated by specific factors. Among thirteen Abhyantra srotas Pranavaha is one. Its main function is to provide the medium, through which Prana flows, which is governed by Vata. General causes of vitiation of Pranavaha Srotas include suppression of natural urges; seasonal, environmental, lifestyle and dietary patterns that are Ruksha, Sita in nature; exertion and exercise while hungry etc. they produce different symptoms like Kasa, Svasa, Hikka etc. Though Brihatrayeekaras have mentioned wide range of herbs for treatment of Pranavaha Sroto Vikaras, Charaka has mentioned around 30 drugs in 3 categories related to Pranavaha srotas i.e. Kasahara, Svasahara and Hikkahara Dasaimanis while Susrutha and Vagbhata has mentioned Svasa and Kasahara dravyas in Ganas like Surasadi and Vidarigandhadi ganas. Apart from these a lot of drugs are mentioned in their respective treatments. Among these the drugs like Sati, Puskaramoola, Abhaya, Trikatu, Brihati, Kantakari, Tamalaki, Tulasi are very frequently mentioned for the treatment of different Pranavaha Sroto vikaras. In the present paper research activities carried out around the world on different herbs used in the Pranavaha sroto vikaras are reviewed which will provide a scientific rationale of using them in Ayurveda.